ANALISIS PERENCANAAN JALUR SIRKULASI NEW PEDSTRIAN PADA KAWASAN KOMERSIAL JL. BOULEVARD DAN JL. PENGAYOMAN, KOTA MAKASSAR - Arinda Wahyuni; Gusti Hardyanti Musda; Ahmad Nadhil Edar; Arsyil, Arsyil (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
This research focuses on the planning of new pedestrian routes, including underpasses and skywalks, in the commercial areas of Jalan Boulevard and Jalan Pengayoman, Makassar City. The main problem faced is the lack of comfort and safety of pedestrian paths due to illegal parking, congestion, and limited pedestrian facilities. The research aims to design a pedestrian path that is standardized, comfortable, and integrated with strategic areas. The methods used include field observations, interviews, and analysis of primary and secondary data. The results showed that the majority of respondents supported the development of pedestrian paths and skywalks with important elements such as adequate lighting, accessibility for people with disabilities, and supporting facilities such as seating and clear direction markers. The path design is designed to connect with public transport hubs, shopping centers, and office areas, prioritizing convenience, safety, and sustainability. This research provides design recommendations based on regulations such as Technical Guidelines No. 027/T/Bt/1995 and Permen PUPR No. 5 of 2023. The implementation of new skywalks and pedestrian paths is expected to improve the quality of public spaces, reduce congestion, and create a more comfortable, efficient, and inclusive urban environment.